2014
DOI: 10.4141/cjps2013-043
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound to discern differences in Asian noodles prepared across wheat classes and between varieties

Abstract: Use of ultrasound to discern differences in Asian noodles prepared across wheat classes and between varieties. Can. J. Plant Sci. 94: 525Á534. Nine wheat varieties, five Canada Western Red Spring (CWRS) and four Canada Prairie Spring Red (CPSR), grown at the same locations and composited by variety, were milled to yield 65% extraction flours, which were used to form yellow alkaline raw and cooked noodles. The CWRS flours were Â2% higher in protein content than the CPSR varieties, with varieties within each cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The ability to perform measurements on single noodle sheets offers significant advantages in time and material over our previous investigations employing multiple layers of raw noodles Hatcher 2010, 2011;Diep et al 2014;Hatcher et al 2014). The ability to perform measurements on single noodle sheets offers significant advantages in time and material over our previous investigations employing multiple layers of raw noodles Hatcher 2010, 2011;Diep et al 2014;Hatcher et al 2014).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The ability to perform measurements on single noodle sheets offers significant advantages in time and material over our previous investigations employing multiple layers of raw noodles Hatcher 2010, 2011;Diep et al 2014;Hatcher et al 2014). The ability to perform measurements on single noodle sheets offers significant advantages in time and material over our previous investigations employing multiple layers of raw noodles Hatcher 2010, 2011;Diep et al 2014;Hatcher et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Flour (50 g), 34% water (w/w), 1% (w/w) NaCl, and 1% w/w kansui (9:1w/w sodium and potassium carbonate) dissolved in the water, with or without 75 U of GOx (Sigma-Aldrich, Saint Louis, MO, U.S.A.), were mixed with a centrifuge mixer (SpeedMixer DAC 150FV, FlackTek, Landrum, SC, U.S.A.) for 30 s at 3,000 rpm (Diep et al 2014). The wheat represented a composite of CWRS samples collected across western Canada during the 2011 harvest and was milled to a 72% flour extraction level with an Allis-Chalmers mill.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flour (50 g), 34% water (w/w), 1% (w/w) NaCl, and 1% (w/w) kansui (9:1 sodium and potassium carbonate) were mixed with a centrifuge mixer (SpeedMixer DAC 150FV, FlackTek, Landrum, SC, U.S.A.) for 30 s at 3,000 rpm (Diep et al 2014). A strong flour blend was milled from two Canada Western Red Spring wheat class varieties to 72% flour extraction with an Allis-Chalmers mill.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of the ultrasound technique as a means of screening for wheat variety discrimination has been limited to a few research studies (Alava et al, 2007;Diep, 2014;Garcia-Alvarez et al, 2006;Kidmose et al, 2001). Also, Diep et al (2014) reported the sensitivity of ultrasound velocity and attenuation coefficient, obtained at the frequency of 40 kHz, to differences between raw Asian noodles prepared from several Canadian wheat varieties. Also, Diep et al (2014) reported the sensitivity of ultrasound velocity and attenuation coefficient, obtained at the frequency of 40 kHz, to differences between raw Asian noodles prepared from several Canadian wheat varieties.…”
Section: Low-intensity Ultrasoundmentioning
confidence: 99%